Decreased quadriceps muscle stiffness on ultrasound elastography is associated with sarcopenia in end-stage kidney disease - Chiu, Chien-Hua; Chen, Jia-Feng; Yu, Shan-Fu; Hsu, Chung-Yuan; Chen, Ying-Chou (Frontiers in Nephrology, 2025)
BackgroundSarcopenia has emerged as one of the major complications in end-stage kidney disease (ESKD), leading to greater disability and poor long-term outcomes. This study aimed to compare quadriceps muscle sonoelastographic parameters between ESKD patients with and without sarcopenia.Materials and methodsWe prospectively enrolled 50 ESKD patients with sarcopenia and 50 ESKD patients without sarcopenia as controls. All participants underwent clinical and laboratory evaluation, sonoelastography of the quadriceps muscle, and dual-energy X-ray absorptiometry (DXA) for muscle mass assessment. Sarcopenia was diagnosed according to the revised European Working Group on Sarcopenia in Older People (EWGSOP2, 2019), which emphasizes muscle strength as the principal determinant. Handgrip strength, gait speed, and appendicular skeletal muscle mass (ASM/height²) by DXA were assessed. The elastography ratio was calculated as the stiffness of the quadriceps muscle relative to the overlying subcutaneous tissue. Comparisons were made between the sarcopenia and non-sarcopenia groups.ResultsA total of 100 ESKD patients were included: 50 with sarcopenia (mean age, 63.0 ± 12.7 years) and 50 without sarcopenia (mean age, 58.3 ± 14.9 years). The sarcopenia group demonstrated a lower quadriceps-to-subcutaneous tissue elastography ratio compared with the control group. Multivariate logistic regression identified the quadriceps-to-subcutaneous tissue ratio, muscle hardness, and body mass index (BMI) as independent predictors of sarcopenia (p < 0.05). Lower BMI was associated with an increased risk of sarcopenia. The optimal quadriceps-to-subcutaneous tissue elastography ratio cut-off value was 0.885 (sensitivity 82.4%; specificity 66.7%).ConclusionSonoelastography provides a reliable and non-invasive assessment of quadriceps muscle stiffness and demonstrates good predictive value for detecting sarcopenia in ESKD patients. Given its accessibility, low cost, and ease of use, sonoelastography may serve as a valuable adjunct to conventional DXA in evaluating muscle quality in this high-risk population.